2012
DOI: 10.5455/medarh.2012.66.409-411
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Lipid Accumulation Product in Corelation to Body Mass Index in Women with Polycystic Ovary Syndrome

Abstract: Patients with PCOS and BMI < or = 24.9 kg/m2 were significantly different from those with BMI > 25 kg/m2 in the values of body weight, waist circumference and triglycerides. There was no statistically significant difference in insulin resistance. LAP values were higher in patients in the group with BMI > 25 kg/m2. LAP was a marker for differentiation of insulin--resistant and non-resistant women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…14 LAP has been demonstrated to be a good discriminator of glucose intolerance and diabetes by a variety of studies. 16,[24][25][26][27][28][29][30][31] Moreover, LAP has been reported to predict all-cause and cardiovascular mortality. [32][33][34][35] However, further studies are needed to determine whether LAP is better for predicting cardiovascular events than are other adiposity markers, including BMI, WC, waist-to-height ratio, and waist-to-hip ratio.…”
Section: Discussionmentioning
confidence: 98%
“…14 LAP has been demonstrated to be a good discriminator of glucose intolerance and diabetes by a variety of studies. 16,[24][25][26][27][28][29][30][31] Moreover, LAP has been reported to predict all-cause and cardiovascular mortality. [32][33][34][35] However, further studies are needed to determine whether LAP is better for predicting cardiovascular events than are other adiposity markers, including BMI, WC, waist-to-height ratio, and waist-to-hip ratio.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is not clear whether there is any difference between the most appropriate adiposity indexes of women with PCOS and the normo-ovulatory non-hirsute women (8). Several efforts have been made to compare the optimum obesity marker for women with PCOS with normal control subjects (8,9,10), but the majority of these studies are based on the measurements performed in women with PCOS referred to clinics (42,43,44,45,46), which may not yield reliable estimations. In addition to small samples, these studies are restricted by the lack of comparison of various available adiposity markers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is still not clear as to which of the various simple and complex adiposity indexes could precisely predict the metabolic disturbances (8,9,10) and whether these indexes are different in women with PCOS compared with normoovulatory non-hirsute women (8). It has been shown that the BMI cannot be efficiently used to precisely predict CVD risk (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Subclinical hypothyroidism is difficult to diagnose and is often overlooked. Adequate diagnosis requires: conducting more extensive laboratory tests in relation to the performance of routine TSH test from time to time should be practiced by monitoring the temperature of the body, and careful monitoring of clinical signs and history of the disease (1,18,19,20,21).…”
Section: Discussionmentioning
confidence: 99%